Прийняття управлінських рішень при визначенні підприємства з більшим інноваційним потенціалом на основі методу аналізу ієрархій - Коцюк, О. (Видавництво Національного університету «Львівська політехніка», 2000)
Описано, як за допомогою одного із методів системного аналізу (методу аналізу ієрархій) можна порівняти інноваційний потенціал підприємств. The articles deals with aspects of applying methods of expert estimates to ground managerial decisions. One of such methods is the hierarchy analysis which allows to split the problem into parts and present it as an hierarchy. This method allows to process non-numerical data and may be used in situation when decision is taken intuitively.